Penggunaan Media Video Pembelajaran Untuk Meningkatkan Hasil Belajar Matematika Siswa di Sekolah Dasar - Marjania Afifa; Nur Azmi Alwi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Technological developments, especially digital technology, require teachers to use media in the learning process. This learning media is one of the important factors that supports learning. With the existence of learning media, it is hoped that learning objectives can be conveyed well. This research aims to determine the effect of instructional video media on improving student learning outcomes in mathematics subjects in elementary schools. This research uses the SLR (Systematic Literature Review) method. Data collection was obtained by documenting scientific articles related to the same research. The articles obtained and used in this research were 8 national journal articles obtained from the Google Scholar database using the publish or perish application. Based on the research results, it can be concluded that learning video media can improve elementary school students' mathematics learning outcomes.